Dis/connection: Violence, Religion, and Geographic Imaginings in Aceh and Colonial Indonesia, 1890s–1920s. Issue 3 (December 2021) - Kloos, David
Abstract : This article draws attention to the case of Aceh to analyse the mechanisms through which ideologically driven geographic imaginings obscured the role of place and class in colonial and anti-colonial violence in Indonesia. Its main perspective is the region's West Coast. In the course of the long and brutal Dutch-Acehnese war (1873–1942), the West Coast of Sumatra was transformed from a dynamic centre of trade, commerce, and religious renewal into a colonial frontier. Violent resistance persisted in this area as the Dutch involved themselves in and exacerbated local contestations for authority and resources. Colonial discourse worked to conceal these complexities, foregrounding an image of the West Coast as a remote, backwards, and inherently dangerous place, prone to a violent Muslim millenarianism.